Let the sequence { a n } be defined as:
a n : = ( − 1 ) n + 1 k = 0 ∑ n ( ( 2 k 2 n + 1 ) 2 k )
Evaluate:
n = 1 ∑ ∞ ( 1 + a n 1 )
If the answer is defined as S , find S ( 2 S + 1 ) 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
We rewrite ( 1 + a n ) :
1 + a n = 1 + ( − 1 ) n + 1 k = 0 ∑ n ( ( 2 k 2 n + 1 ) 2 k ) = 1 + ( − 1 ) n + 1 k = 0 ∑ n ( ( 2 k 2 n + 1 ) ( 2 ) 2 k ) = 1 + 2 ( − 1 ) n + 1 k = 0 ∑ n ( ( 2 k 2 n + 1 ) ( ( 2 ) 2 k + ( − 2 ) 2 k ) ) = 1 + 2 ( − 1 ) n + 1 k = 0 ∑ 2 n + 1 ( ( k 2 n + 1 ) ( ( 2 ) k + ( − 2 ) k ) ) = 1 + 2 ( − 1 ) n + 1 ( k = 0 ∑ 2 n + 1 ( ( k 2 n + 1 ) ( 2 ) k ) + k = 0 ∑ 2 n + 1 ( ( k 2 n + 1 ) ( − 2 ) k ) ) = 1 + 2 ( − 1 ) n + 1 ( ( 1 + 2 ) 2 n + 1 + ( 1 − 2 ) 2 n + 1 ) = 2 ( − 1 ) n + 1 ( ( 1 + 2 ) 2 n + 1 + ( 1 − 2 ) 2 n + 1 + 2 ( − 1 ) n + 1 ) = 2 ( − 1 ) n + 1 ( ( 1 + 2 ) n − ( 1 − 2 ) n ) ( ( 1 + 2 ) n + 1 − ( 1 − 2 ) n + 1 ) = 4 ( − 1 ) n + 1 ( 2 2 1 ( ( 1 + 2 ) n − ( 1 − 2 ) n ) ) ( 2 2 1 ( ( 1 + 2 ) n + 1 − ( 1 − 2 ) n + 1 ) )
So if we define { b n } as:
b n : = 2 2 1 ( ( 1 + 2 ) n − ( 1 − 2 ) n )
then, ( 1 + a n ) = 4 ( − 1 ) n + 1 b n b n + 1 , and the desired sum is:
S = n = 1 ∑ ∞ ( 1 + a n 1 ) = n = 1 ∑ ∞ ( 4 ( − 1 ) n + 1 b n b n + 1 1 ) = 4 1 n = 1 ∑ ∞ ( b n b n + 1 ( − 1 ) n + 1 )
For the sequence { b n } , since r = 1 ± 2 satisfies the characteristic equation r 2 = 2 r + 1 , we have the recurrence:
b n = 2 b n − 1 + b n − 2
so the sequence begins 1 , 2 , 5 , 1 2 , 2 9 , 7 0 , 1 6 9 , 4 0 8 , . . . , which we recognize as denominators of fractions that converge to 2 . with the sequence of respective numerators { c n } beginning 1 , 3 , 7 , 1 7 , 4 1 , 9 9 , 2 3 9 , 5 7 7 , . . . , which in fact satisfies the same recurrence.
Since the continued fraction expansion of 2 is [ 1 ; 2 , 2 , 2 , 2 , 2 , . . . ] , the fractions referred to above are the continued fraction convergents to 2 , and we therefore have the theorem that b n + 1 c n − b n c n + 1 = ( − 1 ) n . Thus:
S = 4 1 n = 1 ∑ ∞ ( b n b n + 1 ( − 1 ) n + 1 ) = − 4 1 n = 1 ∑ ∞ ( b n b n + 1 b n + 1 c n − b n c n + 1 ) = − 4 1 n = 1 ∑ ∞ ( b n c n − b n + 1 c n + 1 ) = − 4 1 ( b 1 c 1 − b ∞ c ∞ ) = 4 1 ( b ∞ c ∞ − b 1 c 1 ) = 4 1 ( 2 − 1 )
Notice that 4 S + 1 = 2 , and squaring both sides and simplifying yields:
1 6 S 2 + 8 S + 1 1 6 S 2 + 8 S 8 S ( 2 S + 1 ) S ( 2 S + 1 ) S ( 2 S + 1 ) 1 = 2 = 1 = 1 = 8 1 = 8
and the answer is 8 .